Tingkat Risiko Hewan Liar Wildlife Hazard di Area Airside Bandara Internasional Hang Nadim Batam - Hafifa Hafifa; Rezty Fauziah Novianty Z (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Hang Nadim International Airport in Batam, as one of Indonesia's main airports, plays a vital role in supporting both domestic and international air mobility. However, its proximity to protected forests and green open spaces poses a serious challenge in the form of wildlife hazard risks in the airside area. The main problem identified is the potential for flight disturbances and accidents caused by the presence of wild animals such as birds, monkeys, stray dogs, and cats, which can lead to incidents like bird strikes and Foreign Object Debris (FOD). This study aims to determine the level of wildlife hazard risk in the airside area of Hang Nadim International Airport and to provide effective control recommendations to improve aviation safety. This research uses a descriptive method with qualitative and quantitative approaches. Data were collected through field observations, interviews with relevant staff, and documentation of wildlife hazard incidents that occurred from 2022 to early 2024. Risk analysis was carried out using the Hazard Identification and Risk Assessment (HIRA) method, by identifying the types of wild animals that frequently appear, the frequency of incidents, and the impact on airport operations. The results show that the level of wildlife hazard risk in the airside area of Hang Nadim International Airport is categorized as moderate to high, especially for incidents involving birds and monkeys. Events such as aircraft delays during takeoff or landing, as well as the discovery of animal carcasses on the runway, indicate the need for more effective management. Therefore, wildlife hazard risk management must be a priority to ensure the safety and smooth operation of flights at Hang Nadim International Airport.